2016
DOI: 10.1111/1365-2435.12729
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometers can measure total and activity‐specific energy expenditures in free‐ranging marine mammals only if linked to time‐activity budgets

Abstract: Summary Energy expenditure is an important component of foraging ecology, but is extremely difficult to estimate in free‐ranging animals and depends on how animals partition their time between different activities during foraging. Acceleration data have emerged as a new way to determine energy expenditure at a fine scale but this needs to be tested and validated in wild animals. This study investigated whether vectorial dynamic body acceleration (VeDBA) could accurately predict the energy expended by marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 58 publications
7
60
1
Order By: Relevance
“…For example, prey catch attempt (PrCA) behaviours can be identified from peaks in acceleration indicative of rapid head movements (Gallon et al., ; Naito, Bornemann, Takahashi, McIntyre, & Plotz, ; Suzuki, Naito, Folkow, Miyazaki, & Blix, ; Viviant et al., ; Volpov, Hoskins, et al., ), whilst proxies of energetic expenditure (e.g. swimming effort) can be calculated by isolating dynamic movement rates (Jeanniard‐du‐Dot, Guinet, Arnould, Speakman, & Trites, ; Sato, Mitani, Cameron, Siniff, & Naito, ; Volpov, Rosen, Trites, & Arnould, ). The latter of these can additionally be used in tandem with estimations of pitch and vertical speed to give a relative measure of body condition (Aoki et al., ; Richard et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, prey catch attempt (PrCA) behaviours can be identified from peaks in acceleration indicative of rapid head movements (Gallon et al., ; Naito, Bornemann, Takahashi, McIntyre, & Plotz, ; Suzuki, Naito, Folkow, Miyazaki, & Blix, ; Viviant et al., ; Volpov, Hoskins, et al., ), whilst proxies of energetic expenditure (e.g. swimming effort) can be calculated by isolating dynamic movement rates (Jeanniard‐du‐Dot, Guinet, Arnould, Speakman, & Trites, ; Sato, Mitani, Cameron, Siniff, & Naito, ; Volpov, Rosen, Trites, & Arnould, ). The latter of these can additionally be used in tandem with estimations of pitch and vertical speed to give a relative measure of body condition (Aoki et al., ; Richard et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Jeanniard‐du‐Dot et al . (, their fig. ) present strong relationships between total energy expended and summed DBA across foraging trips in both northern and Antarctic fur seals ( C. ursinus and Arctocephalus gazella ).…”
Section: The Accelerometry Technique Applied To Diving Animalsmentioning
confidence: 96%
“…; Jeanniard‐du‐Dot et al . ,b). And in recent years, I have refereed a number of submitted manuscripts from a host of research groups where analyses have centred around summed values of energy expenditure and DBA to test for evidence that DBA relates to metabolic rate; sometimes other referees for these manuscripts have suggested summing values as an improvement to the analysis.…”
Section: The Time Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on dynamic acceleration can be used to calculate the vector sum of the dynamic body acceleration (VeDBA) or the overall dynamic body acceleration (ODBA), which indicate body motion when G-force values are higher than 0. VeDBA and ODBA values may also provide information about energy expenditure [e.g., Qasem et al, 2012;Jeanniard-du-Dot et al, 2017]. Accelerometer data can be used to derive daily activity budgets [e.g., when an animal moves; Yoda et al, 1999;Lagarde et al, 2008;Grü newä lder et al, 2012;Williams et al, 2014] and, if accelerometer and viewer-observed behavioural data are collected simultaneously, accelerometer data can also be used to characterise behaviours (e.g., walking, running, and leaping) [Sakamoto et al, 2009;Nathan et al, 2012;Graf et al, 2015] and to estimate the energy expenditure associated with different behaviours [Wilson et al, 2006;Qasem et al, 2012;Jeanniard-du-Dot et al, 2017].…”
Section: Introductionmentioning
confidence: 99%